2014
DOI: 10.1289/ehp.1307080
|View full text |Cite
|
Sign up to set email alerts
|

Plasma microRNA Expression and Micronuclei Frequency in Workers Exposed to Polycyclic Aromatic Hydrocarbons

Abstract: Background: Ubiquitous polycyclic aromatic hydrocarbons (PAHs) have been shown to alter gene expression patterns and elevate micronuclei (MN) frequency, but the underlying mechanisms are largely unknown. MicroRNAs (miRNAs) are key gene regulators that may be influenced by PAH exposures and mediate their effects on MN frequency.Objectives: We sought to identify PAH-associated miRNAs and evaluate their associations with MN frequency.Methods: We performed a two-stage study in healthy male coke oven workers to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 37 publications
1
59
2
Order By: Relevance
“…12 These workers were aged between 20 and 60 years old, working in their current workplaces (ie, at the top, side, bottom, and adjacent workplaces of coke ovens, or in offices) for at least 1 year, without recent medication use in the preceding 3 months or self-reported history of chronic diseases, including cancer, chronic inflammation, hypertension, and the serious medical conditions affecting HRV (heart failure, angina, arrhythmia, myocardial infarction, and other non-classified heart problems). We set up multiple monitors in their workplaces and collected the airborne samples with an average flow rate of 2.0 L/min for 6 h. Measurement for PAH in the collected airborne samples was performed by high-performance liquid chromatography as shown in our previous study.…”
Section: Study Populationmentioning
confidence: 99%
See 3 more Smart Citations
“…12 These workers were aged between 20 and 60 years old, working in their current workplaces (ie, at the top, side, bottom, and adjacent workplaces of coke ovens, or in offices) for at least 1 year, without recent medication use in the preceding 3 months or self-reported history of chronic diseases, including cancer, chronic inflammation, hypertension, and the serious medical conditions affecting HRV (heart failure, angina, arrhythmia, myocardial infarction, and other non-classified heart problems). We set up multiple monitors in their workplaces and collected the airborne samples with an average flow rate of 2.0 L/min for 6 h. Measurement for PAH in the collected airborne samples was performed by high-performance liquid chromatography as shown in our previous study.…”
Section: Study Populationmentioning
confidence: 99%
“…Among the 71 PAH-related miRNAs we identified previously, 12 six miRNAs (miR-24-3p, miR-27a-3p, miR-142-5p, miR-320b, miR-150-5p, and miR-126-3p) involved in cardiovascular diseases according to literature review [16][17][18][19][20][21] were chosen in this study to explore their relationships with HRV indices in the validation population (365 coke oven workers) according to our previous study. 12 Four of these miRNAs (miR-24-3p, miR-27a-3p, miR-150-5p, and miR-142-5p) have been detected before. 12 As miRNAs might also interact functionally with environmental factors to affect phenotypes and diseases, 22 we also performed stratification analysis and evaluated the interaction effect between miRNAs and the environmental factors on HRV in this study.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Simultaneously, growing evidences have indicated that exposure to hazardous environmental factors may significantly disrupt miRNA expression patterns (10)(11)(12). Previous studies also revealed that dysregulated miRNAs are involved in responses to polycyclic aromatic hydrocarbons (PAHs) (13). Further studies suggested that miRNAs and their interactions with environmental factors might affect the effects of PAHs exposure on oxidative DNA damage and lipid peroxidation (14).…”
Section: Introductionmentioning
confidence: 99%